The Concept of Justice in the Qur'an and Its Implications for Human Psychology - Aria Panji Saputra; Tazkia Nazilla (al-Afkar, Journal For Islamic Studies, 2026)
One of the principles that must be upheld in Islam is justice. In Islam, justice is a direct command from Allah that must be applied in everyday life, not just an abstract theoretical idea. However, everyone knows that there is still injustice everywhere in our country, both in government, society, and around us. Therefore, Muslims must understand justice from the perspective of the Qur'an in order to apply the values of justice in everyday life, so that social balance and psychological calm can occur among humans. This study uses a qualitative methodology with a focus on library research, with a thematic interpretation approach (maudhu'i). The results of this study are the implications of justice for human psychology: a sense of security and peace, strengthening self-esteem and dignity, reducing social jealousy and resentment, fostering hope and optimism, encouraging sincerity and emotional balance, and the motivation to do good and avoid injustice.